Gender dimension of migration decisions in Ghana: the reinforcing role of anticipated welfare of climatic effect. (3rd June 2019) - Amuakwa-Mensah, Franklin; Sam, Victoria Nyarkoah; Kihiu, Evelyne Nyathira
The concept of migration has been a male phenomenon in time past, however, there has been a change in events as females are gradually gaining dominance in migration patterns in recent times. Using nationwide survey data this paper investigates the determinants of internal migration decisions for males and females in Ghana. We examined whether there is any significant differences in how climate elements together with anticipated welfare gains and socio-economic factors explain internal migration decision of males and females. We find some variations in the determinants of migration decisions for males and female, though these decisions are significantly affected by anticipated welfare gain, socio-economic factors and climate conditions. We observed that females respond more to climate or environmental elements than males. Moreover, the effect of climate on migration decisions for both males and females is reinforced by anticipated welfare gain.